Screening of Potential Key Transcripts Involved in Planarian Regeneration and Analysis of Its Regeneration Patterns by PacBio Long-Read Sequencing - Yang, Yibo; Wang, Peizheng; Jin, Baijie; Dong, Zimei; Chen, Guangwen; Liu, Dezeng (Frontiers in Genetics, 2020)
Dugesia japonica is an excellent animal model for studying the regeneration mechanism due to its characteristics of rapid regeneration and easy breeding. PacBio sequencing was performed on the intact planarians (In) and regenerating planarians of 1 day (1d), 3 days (3d), and 5 days (5d) after amputation. The aim of this study is to deeply profile the transcriptome of D. japonica and to evaluate its regenerate changes. Using robust statistical analysis, we identified 5931, 5115, and 4669 transcripts differentially expressed between 1d and In, 3d and In, 5d and In, respectively. A total of 63 key transcripts were screened from these DETs. These key transcripts enhance the expression in different regenerate stages respectively to regulate specific processes including signal transduction, mitosis, protein synthesis, transport and degradation, apoptosis, neural development, and energy cycling. Finally, according to the biological processes involved in these potential key transcripts, we propose a hypothesis of head regeneration model about D. japonica. In addition, the weighted gene co-expression network analysis provides a new way to screen key transcripts from large amounts of data. Together, these analyses identify a number of potential key regulators controlling proliferation, differentiation, apoptosis, and signal transduction. What’s more, this study provides a powerful data foundation for further research on planarians regeneration.